Efecto de Lactobacillus plantarum sobre la absorción del hierro hémico y no hémico para la formación de hemoglobina en ratas alimentadas con bazo y yema de huevo - Alvarado Bazan, Maricelia Beatriz (2019)
The objective of the present investigation was to evaluate the effect of Lactobacillus plantarum on the absorption of hemic and non-hemic iron for the formation of hemoglobin in rats fed with ram spleen and egg yolk; 30 copies of Rattus rattus race Holtzman were used, distributed in 6 groups (G), with the following treatment: G-1, with physiological saline solution; G-2, with 0.5 mg of commercial iron; G-3, with 0.5 mg of iron contained in egg yolk; G-4, with a suspension of 1.3x1010 CFU / mL of L. plantarum plus 0.5 mg of iron contained in egg yolk; G-5, with 0.5 mg of iron contained in spleen and G-6, with a suspension of 1.3x1010 CFU / mL of L. plantarum plus 0.5 mg of iron contained in spleen. After 10 days of supplementation, after anesthesia, each blood was taken from the abdominal aorta, to determine plasma hemoglobin and serum iron, using the commercial biochemical kits. For the data analyzes, the ANOVA test was used to assess whether there is a significant difference between each group; demonstrating that L. plantarum favors the absorption of iron in groups supplemented with ram spleen (G-5) and ram spleen plus L. plantarum (G-6), obtaining as results 158.48 ug Fe / dL and 167.16 ug Fe / dL respectively. While, in hemoglobin, there was no significant difference in any of the groups.